Symptomatic Profile and Cognitive Performance in Autopsy-Confirmed Limbic-Predominant Age-Related TDP-43 Encephalopathy With Comorbid Alzheimer Disease. Issue 12 (20th October 2022) - Gauthreaux, Kathryn; Mock, Charles; Teylan, Merilee A; Culhane, Jessica E; Chen, Yen-Chi; Chan, Kwun C G; Katsumata, Yuriko; Nelson, Peter T; Kukull, Walter A
Abstract: Transactive response DNA-binding protein 43 kDa (TDP-43) proteinopathy is the hallmark of limbic-predominant age-related TDP-43 encephalopathy neuropathologic change (LATE-NC). LATE-NC is a common copathology with Alzheimer disease neuropathologic change (ADNC). Data from the National Alzheimer's Coordinating Center were analyzed to compare clinical features and copathologies of autopsy-confirmed ADNC with versus without comorbid LATE-NC. A total of 735 participants with ADNC alone and 365 with ADNC with LATE-NC were included. Consistent with prior work, brains with LATE-NC had more severe ADNC, more hippocampal sclerosis, and more brain arteriolosclerosis copathologies. Behavioral symptoms and cognitive performance on neuropsychological tests were compared, stratified by ADNC severity (low/intermediate vs high). Participants with ADNC and LATE-NC were older, had higher ADNC burden, and had worse cognitive performance than participants with ADNC alone. In the low/intermediate ADNC strata, participants with comorbid LATE-NC had higher prevalence of behavioral symptoms (apathy, disinhibition, agitation, personality change). They also had worsened performance in episodic memory and language/semantic memory. Differences narrowed in the high ADNC strata, with worsened performance in only episodic memory in the comorbid LATE-NC group. The co-occurrence of LATE-NC with ADNC is associated with a different pattern of behavioral and cognitive performance than ADNC alone, particularly in people with low/intermediate ADNC burden.